Patient and caregiver outcomes with levodopa-carbidopa intestinal gel in advanced Parkinson’s disease - Francesc Valldeoriola (Nature Portfolio, 2021)
Abstract Levodopa-carbidopa intestinal gel (LCIG) has shown to be efficacious in motor and non-motor symptoms (NMS). Nevertheless, studies with patient Quality of Life (QoL) as a primary endpoint are scarce. To assess the effect of LCIG on Advanced Parkinson’s Disease (APD) patients QoL. Secondarily, the impact on motor symptoms and NMS, emotional well-being, treatment satisfaction, and caregiver QoL, stress, disease burden, anxiety, depression, and work impairment were also investigated. In this prospective, 6-month multicenter postmarketing observational study, LCIG was administered to 59 patients with APD. Endpoints were assessed using validated scales and questionnaires. LCIG significantly improved patient QoL (PDQ-39 mean change ± standard deviation from baseline, −12.8 ± 14.6; P < 0.0001), motor symptoms (UPDRS-III in “On,” −6.5 ± 11.8; P = 0.0002), NMS (NMSS, −35.7 ± 31.1; P < 0.0001), mood (Norris/Bond-Lader VAS, −6.6 ± 21.1; P = 0.0297), fatigue (PFS-16, −0.6 ± 1.0; P = 0.0003), depression (BDI-II, −5.1 ± 9.4; P = 0.0002), anxiety (BAI, −6.2 ± 9.6; P < 0.0001), and patient treatment satisfaction (SATMED-Q, 16.1 ± 16.8; P < 0.0001). There were significant correlations between the change from baseline to 6 months between PDQ-39 and UPDRS-IV, NMSS, BAI, BDI-II, AS, and PFS-16 scores, and Norris/Bond-Lader alertness/sedation factor. Caregiver anxiety also improved (Goldberg anxiety scale, −1.1 ± 1.0; P = 0.0234), but the clinical relevance of this finding is questionable. The serious adverse events reported were similar to those previously described for LCIG. In patients with APD, LCIG improves QoL, motor symptoms and NMS, emotional well-being, and satisfaction with the treatment. Improvement in patient QoL is associated with improvements in motor complications, NMS, anxiety, depression, apathy and fatigue. Improvements in patients’ QoL does not correspond with improvements in caregivers’ QoL or burden.